The Impact of Oil Rent Dependence on Malaysian Manufacturing Sector: The Role of Financial Development and Government Intervention - Chan, Vanessa Ming Miin (Curtin University, 2022)
Oil rent dependence can dampen the manufacturing sector through Dutch disease. This research found that underdeveloped financial sector has weakened the positive relationship between oil rent and the production of manufacturing sector, while government intervention reduces the negative consequences of oil rent on the production of manufacturing sector. Besides, this study found that oil rent dependence does not impact the manufactured exports, while financial development and government intervention do not moderate the relationship between them.